Evaluation of Anti-Diabetic Activity of Datura Stramonium Leaves Extract in Diabetic Swiss Albino Mice - Roshan Kumar Mehta; Ramesh Kohar; Vivek Kumar Mehta; Narayan Gautam; Pradyumna Chaudhary; Mukesh Kumar Chaudhary (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Diabetes mellitus is defined as the increase in blood glucose levels associated with a relative insulin deficiency, insulin resistance or both. Datura stramonium is commonly known as Jimson weed or Datura belongs to family Solanaceae containing different types of alkaloids, saponins, tannins, steroids, flavonoids, phenols and glycosides. MATERIAL AND METHODS Extraction was done by maceration process using ethanol as solvent. Swiss albino mice of 20-35 gram were taken as study animal. Diabetes was induced by using Alloxan 20 mg/kg body weight and Glibenclamide 10 mg/kg body weight was used as standard. Ethanolic extract of low dose (50 mg/kg) and high dose (100 mg/kg) were subjected for Anti-diabetic activity. RESULTS The extract treated 50 mg/kg, 100 mg/kg and standard 10 mg/kg showed highly significant reduction in blood glucose level (BGL) on 21st and 28th day respectively when compared to negative control group. Extract treated 100 mg/kg showed significant improvement on high density lipoprotein when compared to negative control group. Extract treated 50 mg/kg, 100 mg/kg and standard 10 mg/kg showed highly significant improvement in lipid profile when compared to negative control group. Extract treated 50 mg/kg, 100 mg/kg and standard 10 mg/kg showed significant body weight gain when compared to negative control group. Extract treated 50 mg/kg and 100 mg/kg showed significant improvement in food intake. Extract treated 50 mg/kg and 100 mg/kg showed highly significant but standard treated 10 mg/kg showed significant improvement in water intake. CONCLUSION The present study concludes that the extract possesses potent and significant anti-diabetic activity of Datura stramonium leaves.